2‐Aminoimidazolyl and 2‐Aminopyridyl (S)‐Prolinamides as Versatile Multifunctional Organic Catalysts for Aldol, Michael, and Diels–Alder Reactions. Issue 12 (28th February 2013) - Orlandi, Manuel; Benaglia, Maurizio; Raimondi, Laura; Celentano, Giuseppe
Abstract: The synthesis of multifunctional organocatalysts, easily obtained by the condensation of ( S )‐proline with 2‐aminopyridine, 2, 6‐diaminopyridine, or 2‐aminoimidazole, is reported. These chiral prolinamides promoted the aldol condensation between cyclohexanone and different aromatic aldehydes with moderate to very high enantioselectivities (up to 98  % ee ), depending on the nature of the substituents on the aryl ring. Computational studies were performed to clarify the stereochemical behaviour of the two different types of catalysts and to understand the role of the different structural components of the chiral prolinamides in the recognition processes between the catalysts and the reactants. In preliminary experiments, trifluoroacetate salts of the chiral prolinamides have been used for the first time as catalysts in Diels–Alder reactions between cyclopentadiene and cinnamaldehyde and in Michael reactions. Abstract : The synthesis of multifunctional organocatalysts, easily obtained by the condensation of ( S )‐proline with 2‐aminopyridine, 2, 6‐diaminopyridine, or 2‐aminoimidazole is reported. These chiral prolinamides promoted the aldol condensation between cyclohexanone and different aromatic aldehydes (up to 98 % ee ), and also catalysed Diels–Alder and Michael reactions.